2002
DOI: 10.1291/hypres.25.335
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Pulse Pressure Relates to Diabetes Mellitus and Low HDL Cholesterol, but Not to Hyperlipidemia in Hypertensive Patients Aged 50 Years or Older.

Abstract: Higher pulse pressure is associated with higher cardiovascular risk. We investigated the relationship between pulse pressure and known metabolic risk factors in hypertensive patients who had not experienced stroke or myocardial infarction. In a multicenter cross-sectional survey made in 1995, we registered 939 hypertensive patients aged 50 years. Of these, 734 had never experienced stroke or myocardial infarction. We divided these 734 patients into two groups

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 44 publications
1
11
0
2
Order By: Relevance
“…This finding was in accordance with research that has suggested a close relationship between diabetes mellitus and increased arterial stiffening [23][24][25]. Contrary to a few studies that failed to detect any significant increase in the stiffness of the elastic artery in patients with diabetes [26,27], our results were aligned to Miyagi et al [28], who demonstrated that PP was significantly associated with having diabetes. It is important to note that PP is a risk factor for arterial stiffness and that there are direct measures such as noninvasive ultrasonic imaging [23] and echo tracking systems [24].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding was in accordance with research that has suggested a close relationship between diabetes mellitus and increased arterial stiffening [23][24][25]. Contrary to a few studies that failed to detect any significant increase in the stiffness of the elastic artery in patients with diabetes [26,27], our results were aligned to Miyagi et al [28], who demonstrated that PP was significantly associated with having diabetes. It is important to note that PP is a risk factor for arterial stiffness and that there are direct measures such as noninvasive ultrasonic imaging [23] and echo tracking systems [24].…”
Section: Discussionsupporting
confidence: 93%
“…Diabetes is an independent risk factor for CVD and it has been established that when patients with diabetes develop vascular abnormalities they sustain a worse prognosis for survival than do CVD patients without diabetes [26][27][28]. Our study suggests that PP should also be considered as an important index along with other measures of risk assessment like cigarette smoking, elevated blood pressure, serum lipids levels and hyperglycemia.…”
Section: Discussionmentioning
confidence: 74%
“…It is, however, necessary to confirm the blunted reduction of nighttime PP as a new risk for cardiovascular disease in a prospective study with a large number of the patients. Previous studies (9,10) have shown that diabetes and dyslipidemia are associated with an increase in PP. The present study, however, showed that the elderly patients with a blunted reduction of nighttime PP had higher frequency of smoking, but not higher frequency of diabetes or dyslipidemia.…”
Section: Discussionmentioning
confidence: 92%
“…Miyagi et al reported that the presence of diabetes substantially contributes to the increase in PP (29). Schram et al (30) recently reported that PP was associated with cardiovascular mortality among the diabetic, but not among the nondiabetic individuals who participated in the cohort of the Hoorn Study, suggesting that the presence of diabetes, per se, allows PP to be an independent predictor of cardiovascular events, strokes and deaths.…”
Section: Discussionmentioning
confidence: 99%